Improving Supply Chain Performance Using Lean And Agility Concept - Sim, Ru Min (2014)
Aim- This management project and research aims to investigate lean and agility approaches in supply chains. Through literature reviews, a framework is proposed where lean approach is focused on suppliers while agility is targeted at customers. The feasibility of the framework will be tested through interaction with real industry. This purpose of this management project is not to solve any particular problems but to draw attention to the lean and agility practices of manufacturing organisation supply chains. Methodology- The research methodology for this management project is divided into five parts. The first part is to define the problem statement, research objectives and scope which will help the reader gain better understanding of the subject and theme of the management project. The second part is to conduct literature review found from relevant academic articles from major science-cited journals. After extensive literature review, the third part involves developing conceptual framework to suggest optimal use of lean and agility approaches. Next, the framework is tested through structured interviews conducted with top management of a single organisation. The last part presents the findings, discussion and conclusion. Results- Interview reveals the current practices engaged by the organisation. Some practices are consistent with literature while some are customised particularly for the organisation on a case by case basis. Value- Originality/value: The originality of this paper lies within the context that this paper seeks to address the key relationships and interdependent linkages between lean and agility concepts and supply chain performance within the FMCG industry in Malaysia. To the author’s knowledge, there are no current studies available.